2014
DOI: 10.1097/aog.0000000000000429
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Behavioral Risks for Incident Chlamydia trachomatis Infection in a Prospective Cohort

Abstract: Objective To identify biological and behavioral risks for incident Chlamydia trachomatis among a prospective cohort of young women followed frequently. Methods Our cohort of 629 women from two outpatient sites was seen every 4 months (October 2000 through April 2012) for behavioral interviews and infection testing. C trachomatis was tested annually, and anytime patients reported symptoms or possible exposure using commercial nucleic acid amplification tests. Analyses excluded baseline prevalent C trachomatis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
3
14
1
Order By: Relevance
“…Another potential explanation is that women with lower socioeconomic status may be less likely to participate in CT screening. 31 In line with Aghaizu et al 7 and Hwang et al, 11 we found that women with a high-risk HPV infection at baseline were at increased risk for incident CT infection. In our study, this association remained after controlling for number of sexual partners and condom use, indicating that the increased risk of CT infection was not explained by more risk-taking sexual behavior among the HPV-positive women.…”
Section: Incident Ct Infectionsupporting
confidence: 85%
See 4 more Smart Citations
“…Another potential explanation is that women with lower socioeconomic status may be less likely to participate in CT screening. 31 In line with Aghaizu et al 7 and Hwang et al, 11 we found that women with a high-risk HPV infection at baseline were at increased risk for incident CT infection. In our study, this association remained after controlling for number of sexual partners and condom use, indicating that the increased risk of CT infection was not explained by more risk-taking sexual behavior among the HPV-positive women.…”
Section: Incident Ct Infectionsupporting
confidence: 85%
“…Furthermore, inconsistent findings may be caused by the potentially complex interactions between condom use and risk-taking sexual behavior of the women and their partners. 11 Regarding educational level, we found that women with low educational level were at higher risk for incident CT infection, and this association remained after adjusting for age and sexual behavior. Similar results were obtained in other studies, but these estimates were not adjusted for potential confounders.…”
Section: Incident Ct Infectionmentioning
confidence: 80%
See 3 more Smart Citations